Design of anisotropic focusing metasurface and its application for high-gain lens antenna. (31st January 2017) - Guo, Wenlong; Wang, Guangming; Li, Haipeng; Li, Tangjing; Ge, Qichao; Zhuang, Yaqiang
Abstract: In this paper, we propose an anisotropic focusing metasurface with function of focusing orthogonally polarized waves in refraction and reflection modes respectively. By employing four layered metallic patches spaced by triple layered dielectric spacers, an anisotropic phase element is designed with capability of transmitting x -polarized waves but reflecting y -polarized beams efficiently. Composed of 21 × 21 cells and with size of 105 × 105 mm 2, a focusing metasurface operating at 15 GHz is designed with the same focal length of 30 mm for x - and y -polarized waves. By setting a patch antenna at the focal point, the metasurface sample is employed to enhance gain of the radiation source. For verification, the metasurface sample is fabricated and measured. The antenna performance, in terms of realized boresight gain and operating bandwidth under x - and y -polarized waves illumination, is presented. Results show that the 1 dB gain bandwidths are respectively from 14.7 to 15.3 GHz and 14.7 to 15.2 GHz, and the gain are enhanced by 14.1 dB, 15.1 dB in refraction and reflection modes when the metasurface is impinged by x - and y -polarized spherical waves. The proposed anisotropic metasurface may afford an alternative for designing anisotropic planar lens or high-gain antenna.